Effect of early initiation of steroid-sparing drugs in patients with bullous pemphigoid - Fenne, Inger Johanne; Askildsen Oftebro, Guro; Vestergaard, Christian; Frølunde, Anne Sofie; Bech, Rikke (Frontiers in Immunology, 2023)
Introduction Bullous pemphigoid (BP) can be treated using systemic and topical glucocorticoids and/or other immunomodulatory agents. However, the long-term use of systemic glucocorticoids causes severe adverse side effects. This study was aimed at investigating whether the early initiation of corticosteroid-sparing therapy (CST) in BP patients results in better outcomes than late or no CST. Method We retrospectively identified all BP patients referred to the tertiary center, of the Department of Dermatology and Venerology, Aarhus University Hospital, Denmark, from 2015 to 2021. Patients’ demographics, comorbidities, treatment, remission of BP, length of admission, relapse, and 1-year mortality were recorded. All patients who received CST were dichotomised into two groups: initiated with CST <28 or >28 days. The groups were compared using t-tests. Additionally, all patients who received CST were compared with those who received systemic glucocorticoids alone. Our cohort was compared with that of a previous study (2006–2013) performed in our department. In 2015, we revised our BP treatment guidelines to include the early initiation of CST. Results On comparing the group of patients initiated with CST <28 versus >28 days, we found no significant differences in the complications or mortality between the groups (p = 0.63 and p=0.79, respectively). The <28 days group had a lower rate of relapse (p < 0.05). On comparing data from this study with those from the previous study, conducted before we revised our treatment guideline, we found a reduced initial dose of prednisolone and reduced admission time in this study. No significant differences were found between patients treated with CST and those treated with systemic glucocorticoids alone. Conclusion The rate of complications and 1-year mortality did not differ significantly between the two subgroups in this study. The relapse rate was lower in the CST <28 days group than in the CST >28 days group. The initial dose of prednisolone and admission time were reduced in this study compared with those in the previous study performed before the implementation of a local treatment guideline recommending the early initiation of CST.